Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1371/journal.pone.0215561
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness assessment of maternal and neonatal health video clips in knowledge transfer using neuromarketing tools: A randomized crossover trial

Abstract: Audiovisual educational material has been used effectively as a knowledge translation strategy in patient education. Given the need to impact maternal mortality rates, 12 video clips related to maternal and neonatal health information were designed based on the results of a previous systematic review (SR). The content was formulated based on clinical practice guideline recommendations and validated following a formal consensus methodology. This study evaluated the effectiveness of knowledge transfer from the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 63 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…When the standard was replaced with emotion-oriented communication, health literacy did not have any statistically significant effect. In the context of maternal and neonatal health clips, results showed that the higher the level of education, the greater the information recall [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the standard was replaced with emotion-oriented communication, health literacy did not have any statistically significant effect. In the context of maternal and neonatal health clips, results showed that the higher the level of education, the greater the information recall [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…The emotional response to health video communication has been reported to be significantly influenced by the age and gender of the recipients. A study by Prieto-Pinto et al [ 68 ] found, by using pupillary dilatation measures, which correlates with autonomous nervous system arousal, that men tend to have a greater emotional reaction after being exposed to maternal and neonatal health video clips. In a study conducted in China that aimed to test video versus virtual reality health communications, Liu et al [ 87 ] found that the young and older population differ in positive emotions after being exposed to communication: the young individuals show a greater emotional response to virtual reality, whereas the older individuals show a greater emotional response to health video communication.…”
Section: Resultsmentioning
confidence: 99%
“…New methods are not only used in testing but also in teaching health literacy, such as audio-visual educational material [ 21 ] or virtual/augmented reality via smartphones [ 22 ] overviewed in Aida et al [ 23 ] In the context of such studies, the use of neuromarketing methods as well as cognitive neuroscience can be seen as new possibilities [ 21 ]. Measuring health may refer to the measurement of general health status through general health measures, measures of physical function, pain measures, social health measures, psychological measures, quality of life measures, and specific disease measures.…”
Section: The Cognitive Processing Of Health-related Information and Its Measurementmentioning
confidence: 99%
“…They are also independent of the subjects’ opinions, claims, and imaginations, which allows for the objective evaluation of engagement levels. Although different physiological measurements, such as electrocardiography (ECG), galvanic skin responses (GSRs), electromyography (EMG), or eye movements (ET) [ 32 ], have been studied, measurements reflecting the subject’s brain activity, such as electroencephalography (EEG) and near-infrared spectroscopy (NIRS) [ 30 , 31 , 33 ], provide the most direct information about a subject’s engagement level.…”
Section: Introductionmentioning
confidence: 99%